Significant Contributions of University Business Incubators in Enhancing the Business Graduates’ Employability and Technopreneurship - Valenzuela, Renalee V. (International Journal of Multidisciplinary: Applied Business and Education Research, 2022)
This study determined the significant contributions of university business incubators (UBIs) in selected higher education institutions in Region II to the business graduates’ employability and technopreneurship. The study also highlights the present situation of the UBIs and the involvement of the business graduates. The method used in the study were mixed quantitative and qualitative analysis. Data were gathered through the administration of a researcher-made questionnaire, interviews, and focus group discussions. Moreover, descriptive statistics were used for the quantitative part, while thematic analysis using in-vivo and free coding was used for the qualitative part. Results revealed that the UBIs under study have adequate facilities and services, develop utility models and seek patents for innovations, assist technopreneurs, start-ups, and businesses, and develop products for different industries. Best practices and challenges were also identified. Involvement with UBIs by business students was self-perceived as high extent, while BI personnel perceived it as low extent. The results led to the development of the UBI's significant contribution model in enhancing the knowledge and skills of the business graduates' employability and technopreneurship. It is pinpointed that BIs can enhance the learning experience of business students through immersion, including it in the development or enhancement of curricula, and developing clear policies and guidelines will benefit business students and other stakeholders.